Translation of Lithuanian Culture-Specific Items into English - Kailėdaitė, Violeta; Asijavičiūtė, Vilma (Kalbotyra, 2005)
The present article sets out to investigate theoretical and practical issues that arise in the process of translating Lithuanian culture-bound items into English. Another major goal of the study is to analyse some of the practices currently employed by Lithuanian translators against the strategies that are proposed by Western scholars working in the field of Translation Studies. The empirical part of the research is based on a selected set of cultural items from the field of folk art.